2015
DOI: 10.1089/vbz.2015.1836
|View full text |Cite
|
Sign up to set email alerts
|

ERIC-PCR Genotyping of SomeCampylobacter jejuniIsolates of Chicken and Human Origin in Egypt

Abstract: The public health importance of the genus Campylobacter is attributed to several species causing diarrhea in consumers. Poultry and their meat are considered the most important sources of human campylobacteriosis. In this study, 287 samples from chicken (131 cloacal swabs, 39 chicken skin, 78 chicken meat, and 39 cecal parts) obtained from retail outlets as well as 246 stool swabs from gastroenteritis patients were examined. A representative number of the biochemically identified Campylobacter jejuni isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
9
8
1
Order By: Relevance
“…This result is in akin with the reports of [ 39 41 ], who have also reported high diversity of Campylobacter species obtained from porcine, avian, turkey, and broiler, respectively. The UPGMA dendrogram clustering image of the 36 C. jejuni isolates genotyped grouped the isolates into four clusters and this finding is in line with the report of [ 42 , 43 ]. Result obtained from C. jejuni fingerprinting is contrary to the report of [ 44 ], who in their report revealed that 15 C. jejuni genotyped were grouped into 10 genotypes with 3 clusters.…”
Section: Resultssupporting
confidence: 88%
“…This result is in akin with the reports of [ 39 41 ], who have also reported high diversity of Campylobacter species obtained from porcine, avian, turkey, and broiler, respectively. The UPGMA dendrogram clustering image of the 36 C. jejuni isolates genotyped grouped the isolates into four clusters and this finding is in line with the report of [ 42 , 43 ]. Result obtained from C. jejuni fingerprinting is contrary to the report of [ 44 ], who in their report revealed that 15 C. jejuni genotyped were grouped into 10 genotypes with 3 clusters.…”
Section: Resultssupporting
confidence: 88%
“…Molecular typing is useful to determine the genetic relationship of pathogens isolated from different sources. Enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC PCR) is a simple, cost effective tool with high discriminatory power for genotyping of different bacterial pathogens [11][12][13]. In order to investigate the occurrence of STEC in Zagazig City, Egypt, minced beef and chicken meat purchased from food outlets and human samples from outpatient clinics at Sharkia Governorate were examined.…”
Section: Introductionmentioning
confidence: 99%
“…ERIC-PCR has been used previously for genotyping of different bacteria including E. coli isolates of different origins in order to determine the genetic relationship between the isolates [11,12,65]. …”
mentioning
confidence: 99%
“…Poultry is recognized as a primary source for Campylobacter spp. transmission to humans as strain of C. jejuni can survive in chicken droppings for up to 6 days after excretion [13]. Comprehensive studies conducted in different Egyptian governorates proved that chickens reared in farms or houses is the main source of Campylobacter infections for contact persons [14][15][16][17].…”
Section: Reservoirs and Transmission Methodsmentioning
confidence: 99%